The home visit as a strategy of health intervention in primary care: the reality of Caicó-RN - Costa, Roberta Kaliny de Souza; Holanda, Cristyanne Samara Miranda de; Azevedo, Dulcian Medeiros de; Gomes, Luana Fabrícia (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objective: to investigate the enforcement and implementation of home visits by the staff of the Family Health Strategy (FHS), in Caicó-RN city. Methodology: this is about an exploratory and descriptive study, from quantitative non-experimental approach, performed with 13 staff nurses who carry out and coordinate activities in teams in the urban area and the data will be obtained through a structured interview, divided into three parts (characterization of occupation, professional training and interview guide). The interviews will be conducted in compliance with the ethical principles of research with human beings. The data will be analyzed and discussed by Microsoft Excel software, using descriptive statistics (absolute and percentage) with figures and tables. Expected results: the intention is to instigate discussion and reflection on the practice of FHS health professionals in the home visit, indicating ways to overcome and improve the health services to the population. Descriptors: home visit; primary health care; the family health program; single health system; family health; community health nursing; health evaluation. RESUMO Objetivo: investigar a execução e implementação da visita domiciliária por parte das equipes da Estratégia Saúde da Família-ESF na cidade de Caicó-RN. Metodologia: trata-se de um estudo de natureza exploratória e descritiva, com abordagem quantitativa não experimental, que será realizado com os 13 gerentes das equipes das ESF da Caicó-RN, enfermeiros que realizam e coordenam as atividades de saúde da zona urbana e os dados serão obtidos por meio de entrevista estruturada, cujo formulário está dividido em três partes (caracterização do profissional, formação do profissional e roteiro de entrevista), respeitando os princípios éticos da pesquisa com seres humanos. Os dados serão analisados pelo Software Microsoft Excel e pela estatística descritiva (absoluta e percentual) com gráficos e tabelas. Resultados esperados: intenta-se instigar discussões e reflexões sobre a prática dos profissionais de saúde da ESF na visita domiciliária, indicando caminhos de superação e melhoria no atendimento dos serviços de saúde à população. Descritores: visita domiciliar; atenção primária à saúde; programa saúde da família; sistema único de saúde; saúde da família; enfermagem em saúde comunitária; avaliação em saúde. RESUMEN Objetivo: Investigar la ejecución y aplicación de las visitas domiciliarias por el personal de la Estrategia de Salud de la Família-ESF, en la ciudad de Caicó-RN. Metodología: la investigación es un estudio exploratorio y descriptivo, con un enfoque cuantitativo no experimental, que se celebrará con el personal de la ESF de la ciudad de Caicó-RN. Los sujetos de la investigación son 13 enfermeras que realizan y coordinan las actividades de salud en los equipos de salud de la familia en el área urbana y los datos obtenidos a través de una entrevista estructurada, dividida en tres partes (la caracterización de la ocupación, la formación profesional y la guía de entrevista ). Las entrevistas se llevarán a cabo en cumplimiento de los principios éticos de la investigación con seres humanos. Los datos serán analizados con la ayuda del software Microsoft Excel, utilizando la estadística descriptiva (absoluta y porcentual), con gráficos y tablas. Resultados esperados: la intención es incitar la discusión y reflexión sobre la práctica de los profesionales de la salud de la ESF en la visita domiciliaria, indicando las maneras de superación y mejoría en el tratamiento de los servicios de salud a la población. Descriptores: visita domiciliaria; atención primaria de salud; programa de salud famíliar; sistema único de salud; salud de la família; enfermería em salud comunitária; evaluación em salud.